Religious statecraft: the politics of Islam in Iran - Tabaar, Mohammad (Columbia studies in Middle East politics, 2018)
In a revisionist reading of Iranian politics since the 1979 Islamic revolution, Mohammad Tabaar demonstrates that the causal link between religious ideology and political order as it has been perceived is perilously misguided. Instead of viewing ideology as a determinant of an actor's political objectives and interests, he examines the religious consequences of politics. The conflict and violence that has been interpreted as an outcome of an ideology should rather be examined as causes of that particular ideology. Tabaar rejects the claim that Shi'a theology independently led to the Islamic Revolution in Iran and shapes its consequences. In actuality, a Shi'a ideology was specifically constructed to engender and preserve the revolution. That is not to say that religion does not matter. Religious ideas, ideals, and ideologies do play critical roles in generating mass mobilization and elite cohesion. It is precisely because political actors are aware of this function that they invest so much political capital in developing and deploying religious ideologies. Tabaar traces half a century of doctrinal changes against the background of Iranian domestic and international politics, and he argues that Islamic ideology is not only used but more importantly is constructed and strategically institutionalized by elites to deal with changing opportunities and threat perceptions